Individual exposure to air pollutants in a Portuguese urban industrialized area - Valente, Joana (2014)
Funding Information: The authors are grateful to the finan cial support of the 3rd European Framework Program and the Portuguese Ministry of Science, Technology and Higher Education, through the Foundation for Science and Technology (FCT), for the postdoctoral grants of J. Valente (SFRH/BPD/78933/2011) and J. Ferreira (SFRH/BPD/40620/2007), and also project INSPIRAR (PTDC/AAC-AMB/103895/ 2008), for the grant to C. Pimentel, supported in the scope of the Competitiveness Factors Thematic Operational Programme (COMPETE) of the Community Support Framework III and by the European Community Fund, FEDER.